2019
DOI: 10.1021/acs.cgd.9b00985
|View full text |Cite
|
Sign up to set email alerts
|

Organic Multifunctional Materials: Second Harmonic, Ferroelectric, and Dielectric Properties in N-Benzylideneaniline Analogues

Abstract: The search for multifunctional organic compounds that display technologically important properties has been pursued in recent years. Here we report the synthesis and structure of a series of single-component N-benzylideneaniline analogues 4-(4-(4-nitrobenzylideneamino)­benzyl)­oxazolidin-2-one (NBOA), 4-(4-(4-chlorobenzylideneamino)­benzyl)­oxa-zolidin-2-one (CBOA), and 4-(4-(4-hydroxybenzy-lideneamino)­benzyl)­oxazolidin-2-one (HBOA). The dynamic disorder observed in the structure of NBOA is investigated usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 44 publications
(60 reference statements)
0
4
0
Order By: Relevance
“…A full search of the CSD for p-substituted benzylideneanilines gave 229 hits for entries that fitted the following criteria: three-dimensional coordinates available, R � 0.075, no disorder, no errors, no polymers, no ions, organics only and only single crystal analyses. An analysis using Mercury (Macrae et al, 2020) of the dihedral angle A/B indicated that it can vary from 0.9 � for (E)-4-{4-[(4-chlorobenzylidene)amino]-benzyl}oxazolidin-2-one (FORYIX; Kumari et al, 2019)…”
Section: Database Surveymentioning
confidence: 99%
“…A full search of the CSD for p-substituted benzylideneanilines gave 229 hits for entries that fitted the following criteria: three-dimensional coordinates available, R � 0.075, no disorder, no errors, no polymers, no ions, organics only and only single crystal analyses. An analysis using Mercury (Macrae et al, 2020) of the dihedral angle A/B indicated that it can vary from 0.9 � for (E)-4-{4-[(4-chlorobenzylidene)amino]-benzyl}oxazolidin-2-one (FORYIX; Kumari et al, 2019)…”
Section: Database Surveymentioning
confidence: 99%
“…However, 1:1 solid solutions of these crystals are elastic, and the 1:2 composition is plastic in nature. Multifunctional organic materials based on N -benzylideneanilines, containing the oxazolidine-2-one functional group, have been exploited as second harmonic generation materials, along with these exhibiting room temperature ferroelectric and dielectric responses …”
Section: Polymorphism Co-crystals and Salts In Pharmaceuticals And Fu...mentioning
confidence: 99%
“…However, two significantly different approaches are currently employed. The materials are supposed to be individually featured for certain utilizations (like in medicine, theranostics is used, or in material science, where a peculiar polymer, with its unique rheological or structural properties, is used), or their high compatibility and multifunctionality (versatile OMs ) are expected.…”
Section: Introductionmentioning
confidence: 99%